Performance metrics and measurements - Arslan, Hüseyin (Wiley, 2021)
This chapter discusses various metrics and measurement techniques discussed to inspect the communication system architecture and its performance. Signal quality estimation is by far the most important measure that can be used in adaptive systems. In addition to various measurements to identify the quality of the signal, visual graphs are also very useful to get insight on impairments and other disturbances impacting the signal. Constellation diagram can be obtained by plotting the imaginary versus the real part of the complex signal. Signal intelligence and generic signal analysis could be extremely important for testing software-defined radio transmitter, especially in doing government regulation, observing an operating network, qualification of a product, and to some extent R&D verification. Reference signal received power measurement, normally expressed in dBm, is utilized mainly to make ranking among different candidate cells in accordance with their signal strength.
Keywords: Cognitive Radio; Performance Metrics; Power Measurement; Signal Quality Estimation; Software-Defined Radio; Visual Inspections